Approximations and possibilities about Struggles content into school environment: an integrative review (Research, Society and Development, 2021)
School Physical Education works with a range of contents that aim to contemplate Movement Corporal Culture, among these are Struggles. Using literature in order to understand how research deals with this topic is essential for understanding its strengths and limitations. Following the integrative review method, this study’s purpose was to identify possible contributions of Struggles over integral human formation of students, into Educational Sports context. A preliminary literature search identified 192 articles published between 2015 and 2020. Studies were evaluated within three categories: Struggles into school environment, teacher formation and Educational Sport aspects. Review resulted to 6 articles according to inclusion and exclusion criteria. Despite limitations around studies on area, results indicate Struggles content is recognized both in educational legislation and by researchers of this field; Physical education professionals have various difficulties for applying Struggles in their classes, mainly alleging problems in their teacher formation; and Educational Sports aspects appear in a non-convincing way, without empirical deepening, nor research applied to this specific theme. It is concluded that Struggles use is possible at school, but it requires confrontations, and Struggles contextualization inside Educational Sport principles is still vaguely explored, making it a field of possibilities for future researches.